Making Eco-Bricks as a Solution to Environmental Problems through Empowering Creative Children: A Case Study in Baruga District, Kendari City - Farida Wardani; Nurul Khotimah (GoAcademica Research & Publishing, 2021)
Garbage is one of the complex problems faced by both developing and developed countries in the world. The waste problem is a common problem and has become a universal phenomenon in various countries in the world. This research uses qualitative research with a descriptive analysis approach. The data used are primary data collected from community-based empowerment activities in the Baruga sub-district, Kendari city. From this research, it can be seen that making eco-bricks can be used as a solution to the use of plastic waste, which is very much in the Baruga sub-district, Kendari City, through creative child empowerment activities. To make products using eco-bricks, glue for PVC plastics is not recommended because the plastic bottles used as eco-bricks are PET plastic, so they are unsuitable if glued with PVC glue.